The Role Of Brand Ambassador And E-WOM In Influencing Purchase Decisions: Mediating Analysis Of Purchase Intention On Scarlett - Lestari, Efa Suci; Lukitaningsih, Ambar; Fadhilah, Muinah (STIE AMKOP, 2025)
This study aims to analyze the impact of Brand Ambassador, E-WOM, and Purchase Intention on Purchase Decision in buying Scarlett products. Scarlett uses Brand Ambassadors and E-WOM as a means to promote products. This research uses quantitative methods with a sample of 140 respondents who are Scarlett consumers who live in the Special Region of Yogyakarta. The sampling technique is to distribute data in the form of a questionnaire and the sample size uses Hair et all because the population is not known with certainty. The measuring instrument used is validity and reliability tests and data analysis techniques using multiple linear regression models with the help of SPSS 25. The results of this study prove that the hypotheses are not all accepted, namely, brand ambassadors have no effect on purchase decisions, while E-WOM and purchase intention affect purchase decisions. This shows that only the E-WOM and purchase intention variables have a significant effect on purchase decision. The results of this study also show that the Purchase Intention variable is able to mediate the relationship between Brand Ambassador and E-WOM on Scarlett product Purchase Decision. This study recommends that Scarlett focus on promotion through E-WOM, and companies are expected to be able to choose the right Brand Ambassador, and maintain Purchase Intention consistency to increase Purchase Decision. Keywords: Brand Ambassador, E-WOM, Purchase Intention, Purchase Decision.